We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
162
1
avatar

Here's the function: \(4 - y = {\sqrt{3x}}\)

 

I keep on getting \(y = {-\sqrt{3x}} + 13\), which I know is wrong when I compared the two functions graphically.

 Oct 15, 2018

Best Answer 

 #1
avatar+104384 
+3

HUH?

\(4 - y = {\sqrt{3x}}\\ 4 = {\sqrt{3x}}+y\\ 4 - {\sqrt{3x}}=y\\ y=4 - {\sqrt{3x}}\)

 

 

 Oct 15, 2018
 #1
avatar+104384 
+3
Best Answer

HUH?

\(4 - y = {\sqrt{3x}}\\ 4 = {\sqrt{3x}}+y\\ 4 - {\sqrt{3x}}=y\\ y=4 - {\sqrt{3x}}\)

 

 

Melody Oct 15, 2018

16 Online Users

avatar
avatar
avatar